2016
DOI: 10.1111/dom.12824
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of nausea, vomiting and diarrhoea reported as adverse events in clinical trials studying glucagon‐like peptide‐1 receptor agonists: A systematic analysis of published clinical trials

Abstract: GLP-1 RAs are associated with gastrointestinal AEs that are related to dose and background medications (especially metformin) and may vary in a compound-specific manner. Long-acting agents are associated with less nausea and vomiting but with more diarrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
183
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(205 citation statements)
references
References 59 publications
17
183
1
1
Order By: Relevance
“…Discontinuation due to nausea was low and not dose dependent. The incidence reported in this study was comparable to the incidence reported with other GLP-1 RAs (17,18).…”
Section: Discussionsupporting
confidence: 86%
“…Discontinuation due to nausea was low and not dose dependent. The incidence reported in this study was comparable to the incidence reported with other GLP-1 RAs (17,18).…”
Section: Discussionsupporting
confidence: 86%
“…Although improvement in glucose metabolism has been repeatedly confirmed in 724 numerous preclinical and clinical studies, higher doses of GLP-1 are required to achieve a meaningful decrease in body weight. Furthermore, GLP-1 agonism confers dose-dependent gastrointestinal adverse effects that serve to limit the therapeutic intensity (Peters, 2013;Bettge et al, 2017). Nevertheless, when used as an adjunct to lifestyle changes, Saxenda (3 mg liraglutide; Novo Nordisk) is approved by the FDA for treatment of obesity.…”
Section: A Optimized Glucagon-like Peptide 1 Monoagonistsmentioning
confidence: 99%
“…В одном метаанализе АР ГПП-1, вводимые 1 р/нед, были более эффективны, чем эксенатид, вводимый 2 р/сут, в снижении уровня HbA 1c и сопровождались сравнимой динамикой массы тела и частотой гипогликемии [22]. В другом метаанализе АР ГПП-1 (включая лираглутид) были ассоциированы с более низкой частотой тошноты и рвоты, но с более высокой частотой диареи, чем АР ГПП-1 короткого действия [45]. Еще в одном метаанализе было показано, что снижение массы тела по сравнению с инсулинотерапией при применении АР ГПП-1 длитель-ного действия (включая лираглутид) обычно меньше, чем при применении АР ГПП-1 короткого действия [46].…”
Section: сравнение ар гпп-1unclassified